2020
DOI: 10.18494/sam.2020.2674
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Lathe Cutting Parameters Using Taguchi Method and Grey Relational Analysis

Abstract: In the current precision industry, the rapid production of high-quality parts in bulk quantities has led to high competitiveness. In this study, the Taguchi method and grey relational analysis (GRA) approach were used in a practical investigation of precision lathe processing. The purpose was to find optimal parameters for single-target and multitarget cutting. The production of targets of the highest quality was the research focus, with the aim of strengthening the links between this study and the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…Mahmoudian et al [10] performed methyl-methacrylate polymerization to improve the reciprocation of nanoparticles, and Costa et al [11] optimized the process factors of the steel turning process using the Taguchi method. Bo-Lin Jian et al [12] optimized the cutting parameters for precision lathes via the Taguchi method. Their study showed that the cutting depth and spindle speed have the greatest impact, and directly affected the surface roughness of the product and the material removal rate.…”
Section: Introductionmentioning
confidence: 99%
“…Mahmoudian et al [10] performed methyl-methacrylate polymerization to improve the reciprocation of nanoparticles, and Costa et al [11] optimized the process factors of the steel turning process using the Taguchi method. Bo-Lin Jian et al [12] optimized the cutting parameters for precision lathes via the Taguchi method. Their study showed that the cutting depth and spindle speed have the greatest impact, and directly affected the surface roughness of the product and the material removal rate.…”
Section: Introductionmentioning
confidence: 99%